Leadership and job satisfaction - Moey, Soo Foon (IIUM Press, International Islamic University Malaysia, 2017)
The issue of job satisfaction is not peculiar to Malaysia but throughout the world. Job satisfaction can curb the intention to resign among highly qualified academic staff which can affect the status of the nursing faculty and the learning environment. The nursing colleges under the Ministry of Health Malaysia (MOH) were not spared from this scenario. Therefore, the study was conducted to find out the main factors contributing to the above matter. As nursing education increases its complexity, good leadership and effective educators are vital for greater college performance and better student achievement. Studying effective leadership styles and applying them in the nursing faculty can be beneficial to job satisfaction which can aid in augmenting nursing education. This book seeks to ascertain the causal relationship between the Malaysian nursing academic leadership styles and the moderating effect of demographic factors on nurse educators’ job satisfaction. This mixed method study using a cross sectional survey design and via focus group interview was conducted by obtaining data from nurse educators in the nursing colleges under MOH. The findings indicated that transformational leadership played a highly significant role and also a mediating role between transactional leadership style and nurse educators’ job satisfaction. Job tenure of nurse educators is found to be significant and moderate the relationship between nursing academic leadership styles and nurse educators’ job satisfaction. Additionally, a proposed model of effective academic nursing leadership indicates that effective leadership is enacted via “engaging leadership” where the engaging leader enables the development of an organization modelled by a culture of integrity, transparency, accessibility and genuine valuing of others and their contributions is concerned for the development and well-being of others. This study has helped paved the way for all concerned in understanding the importance of leadership development and training program to improve leadership qualities of nursing academic leaders.